THE STRATEGY OF LOCAL GOVERMENT IN INCREASING THE COMPETITIVENESS OF LAMPUNG SHRIMP EXPORT - Rachmawati, Tety; Lestari, Rahayu; Kamandanu, Fisko Arya; Dani, Dani (Jurnal Hubungan Internasional Indonesia, 2022)
This study aims to analyze the strategy of the local government in increasing the competitiveness of Lampung shrimp exports to be the National Shrimp Barn. The data was obtained by reviewing several primary and secondary documents and in-depth interviews with the Head of the Department of Marine Affairs and Fisheries in Lampung Province. In this study, we use a quantitative approach using RCA (Revealed Comparative Advantage) to find the competitiveness of Lampung shrimp export value and Diamond Porter theory to analyze the strategies in increasing the competitiveness of Lampung Shrimp Export. The results indicate that the competitiveness of Lampung shrimp exports is very strong. The strategy used by Lampung Government to increase the competitiveness of Lampung shrimp exports is by a collaboration between the central and district governments realized by providing access to capital through Kartu Petani Pintar (Smart Farmer Card), technical assistance by forming cross-sector Working Groups (Pokja), and intensive pond constructions in several areas in Lampung.